The Semantic-Pragmatic Characteristics of the Discource of Praise - Gasparyan, Narine (Bulletin of Yerevan University B: Philology, 2024)
One of the means of expressing encouragement is praise. Praise is a sincere positive evaluation of the addressee or a third person, whether  he is present or not in the course of the communication. While praising the addressee or a third person for their actions, praise addressers highly explicit their own emotive state or the emotive attitude towards the facts of speech.Praise is considered a positive evaluative speech act and part of a communication negotiation strategy. When we praise a person, we can motivate them to achieve their goal or dream.Praise is an illocutionary act, which implies the manifestation of the purposefulness of the speech act and expresses the sincere attitude of the speaker towards the interlocutor. The implementation of this act is conditioned by the different status and role characteristics of the communicators.The purpose of the article is to present the semantic and pragmatic peculiarities of speech acts expressing praise.
Keywords: speech act; praise; self-praise; positive assessment; perlocutive result; communicative purpose; intention; addressee